Future Directions for Research on Early Intervention for Young Children at Risk for Social Anxiety. Issue 4 (4th July 2018) - Chronis-Tuscano, Andrea; Danko, Christina M.; Rubin, Kenneth H.; Coplan, Robert J.; Novick, Danielle R.
Abstract : Anxiety disorders are common among young children, with earlier onset typically associated with greater severity and persistence. A stable behaviorally inhibited (BI) temperament and subsequent shyness and social withdrawal (SW) place children at increased risk of developing anxiety disorders, particularly social anxiety. In this Future Directions article, we briefly review developmental and clinical research and theory that point to parenting and peer interactions as key moderators of both the stability of BI/SW and risk for later anxiety, and we describe existing interventions that address early BI/SW and/or anxiety disorders in young children. We recommend that future research on early intervention to disrupt the trajectory of anxiety in children at risk (a) be informed by both developmental science and clinical research, (b) incorporate multiple levels of analysis (including both individual and contextual factors), (c) examine mediators that move us closer to understanding how and why treatments work, (d) be developed with the end goal of dissemination, (e) examine moderators of outcome toward the goal of treatment efficiency, (f) consider transdiagnostic or modular approaches, (g) integrate technology, and (h) consider cultural norms regarding BI/SW/anxiety and parenting.